2006
DOI: 10.1590/s0066-782x2006001400005
|View full text |Cite
|
Sign up to set email alerts
|

Análise de marcadores de estabilização da placa aterosclerótica após evento coronariano agudo

Abstract: With respect to CRP and factor VIIIc, plaque stabilization is suggested in up to three months; IL-6 analysis suggests stabilization as from the third month, although it remained higher than that of the control group for up to six months. Only IL-6 showed prognostic value for further events within a year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
2
2
0
3
Order By: Relevance
“…CRP levels in the CV group are comparable with the levels shown by Schaub et al [33]. Also, Rantes and TNF-a levels in OSA and after an acute cardiovascular event are comparable with the levels demonstrated in previous publications [22,[34][35][36]. Furthermore, IL-8 and sICAM levels in our OSA group are comparable with those published by Al Lawati et al [37].…”
Section: Inflammatory Markers After An Acute Cardiovascular Eventsupporting
confidence: 91%
See 1 more Smart Citation
“…CRP levels in the CV group are comparable with the levels shown by Schaub et al [33]. Also, Rantes and TNF-a levels in OSA and after an acute cardiovascular event are comparable with the levels demonstrated in previous publications [22,[34][35][36]. Furthermore, IL-8 and sICAM levels in our OSA group are comparable with those published by Al Lawati et al [37].…”
Section: Inflammatory Markers After An Acute Cardiovascular Eventsupporting
confidence: 91%
“…Circulating inflammatory markers have been extensively investigated in cardiovascular disease. Indeed, these markers have been found to be key factors in cardiovascular conditions related to atherosclerosis [9] -high expression during acute cardiovascular events being correlated with poorer prognosis -and useful predictors of future events in asymptomatic patients [21][22][23][24]. In a large systematic review, long-term IL-6 levels were shown to be associated with the risk of coronary heart disease [25].…”
Section: Inflammatory Markers and Cardiovascular Diseasementioning
confidence: 99%
“…The average age of individuals in this study and risk factors were comparable to those of most studies of CVDs [20,21]. More women were affected; however, women typically use healthcare services more frequently than men.…”
Section: Discussionsupporting
confidence: 60%
“…MI results from thrombus formation in coronary blood vessels. Such thrombus may cause a stable coronary atherosclerotic lesion to transform into a ruptured plaque [ 3 ]. The process of thrombus formation depends on a number of factors that include inflammatory cells, endothelium, endothelin, cytokines, metalloproteinases, cholesterol and platelets, T-lymphocytes, and phospholipase A2 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%